2006
DOI: 10.1373/clinchem.2005.057810
|View full text |Cite
|
Sign up to set email alerts
|

The Cobalamin-Binding Proteins Transcobalamin and Haptocorrin in Maternal and Cord Blood Sera at Birth

Abstract: Background: Two proteins carry vitamin B 12 in plasma. Transcobalamin (TC) carries ϳ25% of total plasma vitamin B 12 and is 6% to 20% saturated with cobalamin. Haptocorrin (HC) binds ϳ80% of total cobalamin and is largely saturated with cobalamin. Methods: We investigated the distribution and the relationship between concentrations of cobalamin, total and holo forms of TC, and HC in blood samples from pregnant women just before delivery (n ‫؍‬ 92) and in cord blood samples from their newborn babies. We also in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 25 publications
4
43
1
Order By: Relevance
“…Serum cobalamins decrease during pregnancy (Bartels et al, 1989;Willis et al, 1989;Koebnick et al, 2002), but based on the results from our study and a previous study (Dostálová, 1984), it normalizes within a few weeks post-partum. These observations are confirmed by comparing the level of serum cobalamins just before birth measured in a previous study (Obeid et al, 2005) with the level 3 weeks postpartum obtained in our study. Between 3 weeks and 9 months post-partum, we found no alteration in serum cobalamins, and the levels obtained were well in accordance with established reference intervals for non-lactating women, Table 2.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Serum cobalamins decrease during pregnancy (Bartels et al, 1989;Willis et al, 1989;Koebnick et al, 2002), but based on the results from our study and a previous study (Dostálová, 1984), it normalizes within a few weeks post-partum. These observations are confirmed by comparing the level of serum cobalamins just before birth measured in a previous study (Obeid et al, 2005) with the level 3 weeks postpartum obtained in our study. Between 3 weeks and 9 months post-partum, we found no alteration in serum cobalamins, and the levels obtained were well in accordance with established reference intervals for non-lactating women, Table 2.…”
Section: Discussionsupporting
confidence: 91%
“…Comparing the levels of TC and HC obtained 3 weeks postpartum with the levels obtained just before birth using the same ELISA methods (Obeid et al, 2005), the levels of total proteins (TC and HC) seem to decrease significantly at or just after birth, whereas the levels of holoproteins (TC and HC) seem to increase, significantly. In order to explore this observation, a longitudinal study on pregnant women including samples drawn just before and after birth is needed.…”
Section: Discussionmentioning
confidence: 88%
“…Several cross-sectional studies have examined the associations between maternal and neonatal vitamin B-12 status at delivery and have found strong correlations for serum vitamin B-12 and related biomarkers. For example, in a cross-sectional study in Germany, maternal and cord blood holotranscobalamin concentrations were significantly correlated (r = 0.68, P < 0.001) (28). Several cohort studies have noted associations between maternal serum and neonatal (or cord blood) vitamin B-12 concentrations, and some studies found that neonatal vitamin B-12 concentrations were significantly higher than maternal concentrations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Maternal vitamin B-12 concentrations during pregnancy are thought to be closely associated with fetal (28,29) and early infant (30,31) vitamin B-12 status. Vitamin B-12 is transported by haptocorrin and TC; >70% of vitamin B-12 transport across the placenta is facilitated by TC, whereas the remainder is bound by haptocorrin (32).…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin B 12 in serum is bound to 2 proteins, transcobalamin (TC) 3 II and haptocorrin (HC). TC is a 43-kDa nonglycosylated serum protein that is synthesized primarily in the enterocytes and is essential for the transport of vitamin B 12 from ileum into the blood and then into most cells via receptor-mediated endocytosis (1,2 ). TC saturated with vitamin B 12 (holo-TC) constitutes 6%-20% of endogenous circulating vitamin B 12 , whereas unsaturated TC constitutes ϳ90% of TC.…”
mentioning
confidence: 99%